A 36-YEAR-OLD FEMALE PATIENT TREATED WITH AN OCCLUSAL SPLINT: A CASE REPORT - Volcheski, Frosina; Petrovska, Jasna; Aleksova Noveska, Elena; Osmani, Valdeta (Acta medicae Medianae, 2023)
This article describes a case of a 36-year-old female patient who sought help due to long-lasting pain in the temporomandibular joint (TMJ) region. Clinical examination revealed pain on the left side in the region of TMJ, and pain on opening, chewing, and palpation. Also, deviation to the right, and clicking on opening were present. A painful sensation on the left masseter muscle was detected on palpation. The diagnosis was established according to the functional analysis, clinical examination, and obtained anamnestic data. The decision was stabilizing occlusal splint to be administered in combination with exercises, physiotherapy, and symptoms-relieving analgesic treatment if needed. This protocol aimed to alleviate the painful symptomatology and enable relaxation of the muscles of mastication to some degree, before orthodontic treatment. This would obtain a solid basis for stable orthodontic treatment outcomes. Based on the case of the presented patient, it can be concluded that temporomandibular joint disorders (TMJD) can be treated with occlusal splint therapy in combination with exercises and physiotherapy.